Pengaruh Motivasi Kerja, Disiplin Kerja dan Kompensasi terhadap Retensi Karyawan pada PT. Fajar Baizuri & Brothers Kabupaten Nagan Raya - Alisman Alisman; Samriana Samriana; Mawardi Mawardi; Muhammad Andi; Dedi Sufriadi (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
Employees are the main asset for a company in achieving organizational goals. In facing increasingly tight business competition, companies need to retain quality employees in order to maintain productivity and organizational stability. One of the main challenges faced by companies, including PT. Fajar Baizuri & Brothers, is employee retention, where employee retention is caused by various factors, including work motivation, work discipline, and compensation. The purpose of this study was to determine the effect of work motivation, work discipline and compensation on employee retention at PT. Fajar Baizuri & Brothers, Nagan Raya Regency. The location of this research was conducted at PT. Fajar Baizuri & Brothers is located in Gampong Babah Rot, Tadu Raya District, Nagan Raya Regency. The objects in this study are work motivation, work discipline, and compensation on employee retention at PT. Fajar Baizuri & Brothers. Based on the results of the study, it shows that 1) there is an effect of work motivation on employee retention, 2) there is an effect of work discipline on employee retention, 3) there is an effect of work compensation on employee retention, and 4) simultaneously work motivation, work discipline, and compensation simultaneously have a significant and positive effect on employee retention at PT. Fajar Baizuri & Brothers, with the Fcount value (30.662) greater than Ftable (3.114) and the significance value is 0.000.